Fostering Students Writing Skills through the Use of Computer and its Multimedia System in English as a Foreign Language Class in Benin - Hindeme, Ulrich Orlando Sena (Research in English Language Teaching, 2021)
This survey aims to assess the effectiveness of computer and its multimedia system in the teaching and improvement of students writing skills in English as a foreign language. The study adopts the exploratory, qualitative, and the quantitative methods. The study was carried out in public and private secondary schools in Benin and in language centres in the state, during the second semester of the academic year 2019-2020. The respondents involved in this study included 21 teachers and 205 students randomly selected from four chosen schools and language centres. The students belong to class options, A, B, C and D (A, relating to letters, B to human sciences, C to exact sciences, and D, to common sciences) added to advanced level students. Data collection was undertaken through the questionnaires, class observations and interviews. Data analysis was accomplished via the aid of a statistical tool called SPSS (Statistical Package for Social science). The findings revealed that very few teachers in Benin use computer to teach English as a foreign language in their classes. The results also revealed that many students prefer traditional methods of teaching, and very few of them like writing skill. The researcher reached some conclusions and made some suggestions and recommendations.